Pengaruh program mentoring guru terhadap peningkatan kompetensi dan kepuasan kerja - nafi’ah, shabrina yudhitia alfiatun (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of teacher mentoring programs on improving competence and job satisfaction. The mentoring program is designed as a strategic effort to strengthen teachers’ professional abilities through mentoring and sharing of experiences in a systematic manner. The research method used is quantitative with a survey approach, where data is collected through questionnaires and analyzed using inferential statistical techniques. The results of the study show that mentoring programs have a significant positive influence on improving teachers’ pedagogic and professional competence. In addition, mentoring also contributes to increasing job satisfaction, especially in aspects of career development, interpersonal relationships, and work motivation. These findings confirm the importance of implementing mentoring programs in a sustainable manner to support the quality of education and teacher welfare.